HFE-Related Hemochromatosis in a Chinese Patient: The First Reported Case - Zhang, Wei; Wang, Xiaoming; Duan, Weijia; Xu, Anjian; Zhao, Xinyan; Huang, Jian; You, Hong; Brissot, Pierre; Ou, Xiaojuan; Jia, Jidong (Frontiers in Genetics, 2020)
HFE-related Hemochromatosis is the most common genetic iron overload disease in European populations, particularly of Nordic or Celtic ancestry. It is reported that the HFE p.C282Y mutation is present in 1/10 people of northern European descent, resulting in one in two hundred people will be homozygous. However, HFE p.C282Y mutation is virtually absent among East Asians, including Japanese, Koreans, and Chinese. In this article, we report a case of HFE-related hemochromatosis caused by compound heterozygosity HFE p.C282Y/p.R71X. This is the first report of hemochromatosis associated with HFE p.C282Y mutation in China.